Development of Socio-Scientific Issue-Based E-LKPD Flipbook to Improve Elementary School Students' Critical Thinking Skills - Suryani Suryani; Dini Rakhmawati; Achmad Buchori (MASI Mandiri Edukasi, 2026)
The Merdeka Curriculum promotes contextual learning and the development of 21st-century competencies, particularly critical thinking. This study aimed to develop an electronic student worksheet (E-LKPD) in flipbook format based on socio-scientific issues (SSI) and to examine its validity, practicality, and potential to support fifth-grade students’ critical thinking skills. This Research and Development study used the ADDIE model. Participants included two expert validators, one classroom teacher, and 13 fifth-grade students selected through purposive sampling. Data were collected through expert validation, teacher and student response questionnaires, and a one-group pretest-posttest design. The E-LKPD was rated highly feasible by material and media experts, with validity scores of 88.89% and 90.00%, respectively. Teacher and student responses indicated high practicality, with scores of 88% and 95.38%. Students’ mean critical thinking score increased from 46.54 on the pretest to 77.69 on the posttest. A paired-samples t-test showed a statistically significant difference between the scores (p < .001). These findings suggest that the developed SSI-based E-LKPD in flipbook format is valid, practical, and has the potential to support fifth-grade students’ critical thinking skills in science learning.